EFFECT OF ADDING ALOE VERA EXTRACT ON THE QUALITY OF BUFFALO OOCYTES USING TWO CRYOPRESERVATION METHODS - H.T.A., Alkhazraji; H.J.H., Banana; M-B.M.R.Fakhrildin (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was conducted to evaluate the impact of two types of cryopreservation and different concentrations of Aloe vera as an antioxidant (0,10% and 20%) on the viability and normal morphology of immature and in vitro mature buffalo cryopreserved oocytes. The in vitro mature and immature oocytes were kept in cryopreservation solutions for rapid and vitrification techniques. The results revealed that the proportion of buffalo oocytes found to be viable and normal morphology were significantly (P<0.01) higher produced when using a high concentration (20%) of aloe vera on in vitro mature buffalo oocyte which is79.11% and 59.02%; respectively. We conclude from the present study that the viability and normal morphology of post-thawed buffalo cryopreserved in vitro matured oocytes were significantly (P < 0.01) higher produced in using a high concentration of aloe vera than other concentrations of aloe vera, from the side while with other side the vitrification technique than a rapid technique.